Virtual Ethnography of “Padang Halal Tourism”: A Case study on City Branding - Fitri Adona; Yusnani; Sri Nita (CV. AFDIFAL MAJU BERKAH, 2022)
The use of website and social media in government digital marketing has not yet properly known by tourist and potential investors. Mostly the information received was obtained from those who have been into the city, social media organized by private sectors, and netizens. Literally, the social media through the mouth-to-mouth marketing has become the communication channel of the city branding. This research aims at determining the social or cultural environment that influence the selection for social media, messages, and promotional activities used in establishing the brand awareness. Heretofore, the branding of Padang City was not characterized and customized, similar to other cities and regencies in West Sumatera Province. Besides that, the pattern and concept of halal tourism yet have been developed well even though Muslims were the majority of the population. The branding of Padang City has always been identified and integrated into the province, where they were included as the best city in “The best World Halal Tourism Destination“ in Halal Tourism Award 2016. Therefore, this current research applied the virtual ethnographic case study in response to various texts and discursive interpretations on city branding communication related to language approach in communal discussion. The virtual ethnographic adopted from anthropology emphasizes on the importance of researchers’ involvement with the subject being researched in order to get comprehensive understanding on the particular social and cultural environment. The method taken was participant-observation utilizing the internet, where the researchers was immersed within the life of a social and cultural groups in collecting the data, and in gaining the understanding of the groups’ members perspective. This method involves many aspects of qualitative research rather than describing, explaining, or grouping words or actions of a member in a certain community in the internet. Observation and online interaction is regarded as a cultural reflection resulting to deeper understanding. Data collection was performed by having a thorough communication with the member of a particular culture or community such as Muslims community. The communication occurred was in accordance with the needs requiring the involvement, participation, physical contact, interaction, union, relationship, collaboration, and connection among those the members in the community, instead of through websites, servers, or keyboards. In addition, searching the documents in the form of pictures, videos, audios, log books, magazines, symbols, artifacts, and other related objects with the research was also carried out, in order to enrich the data obtained. The results of this research could be used as the recommendation for the government in improving the implementation of city branding, and essentially in developing the city branding theory.